DETERMINANTS OF A TODDLER’S VISIT TO POSYANDU DURING THE COVID-19 PANDEMIC IN JAMBI CITY - Dwinta Elsa Fariza; M.Ridwan; Vinna Rahayu Ningsih (International Journal Of Health Science, 2023)
Introduction, the Covid-19 pandemic and the Large-Scale Social Control Policy (PSBB) have a very significant effect on health services, especially the visit of mothers under five to posyandu. The purpose of this study was to determine the factors that influence the visit of toddler mothers to posyandu at the Kebun Kopi Health Centre, Jambi City. Materials and Methods, this study is descriptive analytic with Cross Sectional approach with accidental sampling technique. The respondents in this study were mothers who had toddlers aged 12-59 months, the working area of the Kebun Kopi Health Centre, Jambi City was 101 people. The analysis in this study used univariate analysis and bivariate analysis using Chi Square. The results/findings, this study showed that the variables related to visits by mothers of toddlers to posyandu during the Covid-19 pandemic were the role of cadres (p = 0.000), family support (p = 0.003) and anxiety (p = 0.034), while unrelated factors were knowledge (p = 0.158), sources of information (p = 0.561), and work (p = 0.290). In conclusion, the factors that influence the visit of mothers of toddlers to posyandu during the Covid-19 pandemic are the role of cadres, family support and anxiety. The need for education about Covid-19 transmission to mothers under five and posyandu strictly implements health protocols.